The impact of rounds with a psychiatry team in the intensive care unit: A prospective observational pilot study evaluating the effects on delirium incidence and outcomes. (April 2023) - Choi, Katherine J.; Tan, Matthew; Jones, Kelly; Sheski, David; Cho, Stephanie; Garrick, Thomas; Yau, Anita; Solio, Donald; Sinclair, Kimberly; Cervantes, Elvin; Castillo, Rae Ann; Clark, Damon; et al.
Abstract: Background: Delirium in the intensive care unit (ICU) is a common but serious condition that has been associated with in-hospital mortality and post-discharge psychological dysfunction. The aim of this before and after study is to determine the effect of a multidisciplinary care model entailing daily ICU rounds with a psychiatrist on the incidence of delirium and clinical outcomes. Objective: To assess the impact of a proactive psychiatry consultation model in the surgical ICU on the incidence and duration of delirium. Methods: This was a prospective, single institution, observational controlled cohort pilot study of adult patients admitted to a surgical ICU. A control group that received standard of care (SOC) with daily delirium prevention care bundles in the pre-intervention period was compared to an intervention group, which had a psychiatrist participate in daily ICU rounds (post-intervention period). The primary outcome was delirium incidence. The secondary outcomes were: delirium duration, ventilator days, hospital and ICU length of stay, and in-hospital mortality. Results: A total of 104 patients were enrolled and equally split between SOC and intervention groups; 95 contributed to analysis. The overall incidence of ICU delirium was 19%. SOC and intervention groups had similar rates of delirium (21% vs 18%, p = 0.72). None of the secondary outcomes statistically significantly differed between the two groups. Conclusion: Delirium in ICU patients is a potentially preventable condition with serious sequelae. There was no difference in delirium incidence or duration between patients receiving SOC or patients who had multidisciplinary rounds with a psychiatrist.